2023
DOI: 10.35848/1347-4065/acb8a5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization as measurement sound source of acoustic cavitation noise from bubble clusters under ultrasonic horn

Abstract: In order to investigate the possibility of using acoustic cavitation noise generated by ultrasonic horns as an acoustic measurement signal, its directional characteristics, autocorrelation characteristics, and frequency characteristics are investigated with a hydrophone and schlieren visualization. In addition, a parabolic mirror is used to shape the spherical acoustic cavitation noise into a planar shape. As a result, it is found that the acoustic cavitation noise consists of a spherical shock wave train and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The schlieren visualization system was the same as in the previous study. 34) Image capture was triggered at 8.8 μs after the hydrophone output exceeded the threshold level. a dagger in Fig.…”
Section: Distribution Of Acoustic Cavitation Noise Originmentioning
confidence: 99%
See 2 more Smart Citations
“…The schlieren visualization system was the same as in the previous study. 34) Image capture was triggered at 8.8 μs after the hydrophone output exceeded the threshold level. a dagger in Fig.…”
Section: Distribution Of Acoustic Cavitation Noise Originmentioning
confidence: 99%
“…As a result, we confirmed that acoustic cavitation noise has steep autocorrelation characteristics with short main lobe full width at half maximum (FWHM) of 87 ns and low side lobe level. 34) Next, we developed an echo sounder employing acoustic cavitation noise, 35,36) and the experiments with a small water tank showed that the echo sounder could successfully measure the target range and spectral sound pressure reflection coefficient in a frequency range between 100 kHz and 5 MHz. However, this experiment highlighted the problem that the acoustic cavitation noise generated by the horn had low spatial coherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) This phenomenon is termed ultrasonic cavitation. [2][3][4][5][6] Because the collapse of bubbles by ultrasound is caused by semi-adiabatic compression, a high-temperature field is generated inside the bubbles, and a chemical reaction occurs. This reaction is termed a sonochemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It can gradually develop into a multiphase, multiscale state that includes small-scale cavity growth and collapse behavior, as well as large-scale cavitation evolution behavior. Meanwhile, cavitation typically results in vibration [1] , erosion [2] , and noise [3] , which can significantly impede the advancement of technology and equipment in high-speed hydrodynamic fields such as underwater weapons, underwater launch, aerospace, fluid machinery, and national defense. Therefore, accurately capturing the bubble structure at various scales and analyzing the transformation Based on high-speed water tunnels and high-speed camera technology, numerous experimental studies have shown that cavitation patterns gradually develop from incipient to sheet, cloud, and supercavitation as the Reynolds number increases or the cavitation number decreases.…”
Section: Introductionmentioning
confidence: 99%